Milk, yogurt, and cheese - Green, Emily K. (Bellwether Media, 2007)
Milk, yogurt, and cheese are rich in calcium and protein. Humans need calcium for strong bones and teeth and protein for muscle development. Kids will find out how milk, yogurt, and cheese help their bodies grow and how many servings they should have every day